2012
DOI: 10.1111/j.1460-6984.2012.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Parent and teacher perceptions of participation and outcomes in an intensive communication intervention for children with pragmatic language impairment

Abstract: This analysis has contributed essential information to the evaluation of SCIP by describing the experience of the intervention as delivered, exploring processes of effective implementation and change in the school setting and by describing the value placed on different outcomes by parents and teachers. These findings can inform planning for collaborations between speech and language therapists and teachers and provide useful information about mechanisms of change in different components of the SCIP interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Such behaviours may be of less concern for parents who may focus more on emotional control, flexibility and self-monitoring. These findings align with those of Iizuka et al (2010) and Baxendale et al (2013) who also found that parent and teacher ratings differed on social communication rating scales.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such behaviours may be of less concern for parents who may focus more on emotional control, flexibility and self-monitoring. These findings align with those of Iizuka et al (2010) and Baxendale et al (2013) who also found that parent and teacher ratings differed on social communication rating scales.…”
Section: Discussionsupporting
confidence: 89%
“…() and Baxendale et al . () who also found that parent and teacher ratings differed on social communication rating scales.…”
Section: Discussionmentioning
confidence: 91%
“…At the same time that molecular genetic paradigms are providing increasingly sophisticated means to examine epigenetic effects (Kraft & DeThorne, 2014), longitudinal case studies offer an opportunity to document the emergence and development of behavior ''in the wild,'' including the multitude of factors likely to impinge upon it. At the very least, both quantitative and qualitative studies should be moving toward the inclusion of more contextual information in the study of child language development, incorporating information across levels from individual biology to social-cultural community (see for example Baxendale, Lockton, Adams, & Gaile, 2013or Zubrick et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Findings generally indicate positive changes in caregivers' perceptions following the initiation of intervention. 16,17 For example, caregivers of toddlers with minimal communication abilities who took part in a caregiver-coached intervention program reported significantly higher expectations for children's communication after completion of the program. 16 In a similar finding, teachers and caregivers of children with pragmatic language impairment reported positive changes in children's communication as a direct result of a social communication intervention.…”
Section: Abstract: Language Disorders Preschool Children Caregiversmentioning
confidence: 99%
“…Caregivers perceived both a greater understanding of intervention targets and positive changes in family dynamics upon completion of the intervention program. 17 Although such findings suggest that caregivers' perceptions of children's language outcomes might improve following treatment, both studies were specific to particular intervention programs and populations of children with communication challenges. More research is needed to characterize caregivers' perceptions of children's outcomes across a wider range of language disorders.…”
Section: Abstract: Language Disorders Preschool Children Caregiversmentioning
confidence: 99%